Hydrophilic adhesive based on lipoic acid derivative sodium salt and preparation and debonding method thereof
By using sodium salt of lipoic acid derivatives in the adhesive, using ionic bonds and high-density hydrogen bonds, the complex processes, environmental pollution and difficulty in detachment of existing adhesives during preparation, storage and use are solved, and high adhesion strength and environmental protection are achieved.
Patent Information
- Application Number
- CN202510304989.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-05-13
AI Technical Summary
There are complex processes, environmental pollution and difficulty in debonding during the preparation, storage and use of existing polymer polymer adhesives, and the adhesion strength is not sufficient to meet higher demands.
A hydrophilic adhesive based on the sodium salt of lipoic acid derivative is used to replace covalent bonds by ionic bonds, and high-density hydrogen bonds are used to improve adhesion strength, and environmentally friendly and easy detachable through water-soluble raw materials.
It achieves low-dose, high adhesion strength and environmentally friendly adhesion effects, low cost, simple process, suitable for industrial production, and has the function of rapid debonding on demand.
Smart Images

Figure CN119979110A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesives, and in particular to a hydrophilic adhesive based on sodium salt of lipoic acid derivatives and a preparation and debonding method thereof. Background Art
[0002] As a common material, adhesives are widely used in industrial production and daily life. They can provide connections between target objects ranging from flexible to rigid to meet different application requirements. At the same time, compared with connection methods such as welding and threaded connections, adhesives are relatively lightweight and low-cost. At the same time, they do not damage the appearance of the target material and have a wide range of uses. At present, most commercial adhesives are based on high molecular polymer materials. Adhesion is achieved through the entanglement of polymer molecular chains and the interaction between the functional groups on the side chains and the adhesion surface. According to the different characteristics of organic polymers, a variety of adhesives with different performances are being continuously developed, such as pressure-sensitive adhesives, structural adhesives, and medical adhesives.
[0003] Common challenges faced by this type of polymer adhesive include complex preparation processes, difficult storage conditions, and reliance on organic solvents during use, all of which have a significant impact on the environment. With the rise of a low-carbon economy, people are paying more and more attention to how to reduce the negative impact of traditional polymer adhesives on the environment. Traditional polymers are difficult to decompose naturally, and the characteristics of adhesives make it difficult to completely remove them from the bonding surface, which not only increases the difficulty of recycling and reuse, but also imposes a long-term burden on the environment. Therefore, the development of new adhesives that are environmentally friendly and easy to recycle has become a top priority.
[0004] The development of new adhesives that are both environmentally friendly and biocompatible, with high-strength adhesion and on-demand debonding properties, has become a research hotspot for scientific researchers. As a natural small molecule compound derived from organisms, lipoic acid not only has good biocompatibility, but is also easy to degrade, fully meeting the standards of environmentally friendly materials. The unique disulfide bonds of lipoic acid have the characteristics of dynamic exchange, which makes the supramolecular materials based on lipoic acid reversible and self-healing. By modifying the side chains of lipoic acid, bionic adhesion functions can be easily achieved, and a series of polymer adhesives with bionic properties can be developed. These materials can not only simulate the adhesion mechanism in nature, but also provide new possibilities for the innovation of environmentally friendly adhesives.
[0005] As a soft material, the lipoic acid polymer material has a low glass transition temperature, which makes the polymer molecular chain easy to slide under the action of external force, which will have a significant negative impact on its adhesion performance. At the same time, relying on the biomimetic adhesion ability of the side chain functional group, the entanglement of the polymer chain will cause the side chain to be unable to fully contact the adhesion surface, and the reduction of the effective contact area will affect the adhesion effect. Subhajit Pal et al. published a research article entitled "Recyclable surgical, consumer, and industrial adhesives of poly (α-lipoic acid)" in the journal Science in 2024 (Science, 2024, 385, 877-883. DOI: 10.1126 / science.ado6292) in the journal Science reported a method for preparing an adhesive by rapid stirring of a solution phase based on lipoic acid small molecules, comprising the following steps: dissolving lipoic acid in ethanol, dissolving another lipoic acid derivative in a small amount of dimethyl sulfoxide, and adding it to the ethanol solution, and then mixing it by vigorous stirring to use it as an adhesive to determine the adhesion strength. The raw materials used in the preparation of the adhesive are hydrophobic covalent organic small molecules, and the use of organic solvents that are harmful to organisms is involved. The shear adhesion strength of the adhesive of the optimal ratio is only 101 ± 9 kPa 2 minutes after bonding, and reaches a maximum of 227 ± 32 kPa after 24 hours of standing. Although the preparation process of the adhesive based on covalent lipoic acid small molecules is relatively convenient and has significant advantages in the field of biological adhesion, the adhesion strength cannot meet higher demands, and the use of covalent cross-linked polymers also brings certain degradation problems. At the same time, in order to achieve the required adhesion strength, more adhesive must be used, which inevitably increases the cost. In addition, how to solve the problem of the amount of adhesive while ensuring high adhesion strength and convenient on-demand debonding still has great challenges. Summary of the invention
[0006] The present invention provides a novel hydrophilic adhesive based on sodium salt of lipoic acid derivative and a preparation method thereof, thereby solving the above-mentioned problems existing in the prior art. Ionic bonds are used instead of covalent bonds to improve the entanglement of polymer materials and solve the problem of high amount of adhesive. High-density hydrogen bonds are used to solve the problem of adhesive strength under low quality. Water-soluble raw materials are used to solve the problem that the adhesive cannot be degraded and cannot be debonded on demand.
[0007] In order to solve the above technical problems, the technical solutions provided by the present invention are as follows:
[0008] A hydrophilic adhesive based on sodium salt of lipoic acid derivative, characterized in that the hydrophilic adhesive comprises a main agent A and a dopant B, and the mass ratio of the main agent A to the dopant B is 1:(0-1);
[0009] The main agent A is a monomer in which lipoic acid and glycine are coupled by an amide bond and exist in the form of sodium carboxylate. Its structural formula is shown in Formula A.
[0010]
[0011] Dopant B is a commercially available raw material, hexamethylenetetramine, and its structural formula is shown in Formula B.
[0012]
[0013] Preferably, the mass ratio of the main agent A to the dopant B in the hydrophilic adhesive is 1:1.
[0014] The present invention also provides a method for preparing the above-mentioned adhesive:
[0015] The method for preparing a hydrophilic adhesive according to claim 1, characterized in that the method comprises the following steps:
[0016] (1) Preparation of Compound 1: Add lipoic acid, N,N'-carbonyldiimidazole (CDI), and dichloromethane to a reaction flask, wherein the molar ratio of lipoic acid: N,N'-carbonyldiimidazole: dichloromethane is 1:(1.1-1.2):(60-90), and stir at room temperature for 30 minutes. Then, add glycine methyl hydrochloride and triethylamine, wherein the molar ratio of glycine methyl hydrochloride: lipoic acid is 1:1, and the molar ratio of triethylamine: lipoic acid is 1.2:1. After stirring at room temperature for 2 hours under nitrogen protection, extract and wash, collect and dry the organic layer, remove the organic solvent by rotary evaporation, and purify by column chromatography to obtain a yellow viscous oily liquid to obtain Compound 1;
[0017] (2) Preparation of main agent A sodium salt of lipoic acid derivative: dissolve the obtained compound 1 in methanol, add a sodium hydroxide aqueous solution with a concentration of 5-10 mol / L, the volume of the sodium hydroxide aqueous solution used should be 1 / 20-1 / 10 of the volume of the methanol used, wherein the molar ratio of the amount of sodium hydroxide solute to compound 1 is (1.1-1.3):1, heat under nitrogen protection and reflux for 2 hours, cool until no longer boiling, add to stirred acetone, and a light yellow to white solid will precipitate, which is collected by filtration, washed and freeze-dried to obtain the target product A;
[0018] (3) dissolving the obtained main agent A thioctic acid derivative sodium salt in water at a concentration of 1.0 g / 12 mL, and adding the dopant B urotropine, wherein the solute mass ratio of the main agent A thioctic acid derivative sodium salt to the dopant B urotropine is 1:(0-1), to obtain the hydrophilic adhesive based on the thioctic acid derivative sodium salt;
[0019] The synthetic route of the main agent A lipoic acid derivative sodium salt monomer is as follows:
[0020]
[0021] The present invention also provides a method for debonding the adhesive, comprising the following steps:
[0022] (1) Place two adhered glass sheets in water and wait for a while to quickly debond and separate the glass sheets.
[0023] (2) Rinse the debonded glass with clean water, wipe dry, and then reuse it.
[0024] Due to the adoption of the above technical solution, the present invention has the following advantages and beneficial effects:
[0025] The main agent A of the adhesive provided by the present invention is a sodium salt of a thioctic acid derivative, and its raw materials come from a small molecule thioctic acid of biological origin, and the basic amino acid glycine, which is rich in sources, low in cost, and has high biocompatibility and little environmental pollution. At the same time, the material synthesis is simple, and no heating or strong acid or strong base is required, which is convenient for large-scale production. The dopant B used is also a commercially available material, which is cheap and easy to obtain. The adhesive of the present invention is low in cost, the process is easy to industrialize, and the product purification is efficient and convenient, and has good economic value.
[0026] The preparation and application methods of the adhesive provided by the present invention are simple and efficient. During preparation, the raw materials only need to be dissolved in water in proportion, thus avoiding the use of organic solvents and facilitating large-scale preparation and transportation. During use, only a very small amount of aqueous solution needs to be dropped on the hydrophilic surface to be adhered, and the amount used is very small. After being flattened, the aqueous solution will disperse spontaneously, ensuring the uniformity of the adhesion area, thus solving the problems of high amount of adhesive used, difficulty in uniform application, poor effect, etc. in the prior art.
[0027] The adhesive provided by the present invention has strong adhesion performance. Under the preferred ratio, 1.0 mg (solute) of adhesive has a strong adhesion performance under the adhesion area of 2.5 cm×2.5 cm (the coating amount is 0.16 mg / cm 2 ), can lift up to 23.8kg, equivalent to 10% of its own weight 7 In the adhesion test of the universal testing machine, the maximum adhesion force can reach about 505N, and the shear adhesion strength can reach 800kPa, which exceeds many adhesives reported in the literature.
[0028] The adhesive provided by the present invention is an environmentally friendly green material with the characteristics of low cost, small amount and excellent performance. Its debonding process is simple and thorough without any residue, which effectively solves the high cost and environmental pollution problems caused by traditional adhesives. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the preparation and use of adhesive.
[0030] Figure 2 It is a bar graph comparing the shear adhesion strength of adhesives with different ratios.
[0031] Figure 3 It is the shear adhesion strength test curve of TG0 adhesive.
[0032] Figure 4 This is the shear adhesion strength test curve of TG0.5 adhesive.
[0033] Figure 5 This is the shear adhesion strength test curve of TG1 adhesive.
[0034] Figure 6 This is the shear adhesion strength test curve of TG1.5 adhesive.
[0035] Figure 7 This is the shear adhesion strength test curve of TG2 adhesive.
[0036] Figure 8 This is the shear adhesion strength test curve of TG2.5 adhesive. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with specific embodiments. Those skilled in the art should understand that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0038] The raw materials and reagents used in the examples of the present invention are all commercially available or prepared using conventional methods in the literature.
[0039] Figure 1 It is a schematic diagram of the preparation and use of adhesive.
[0040] Figure 2 It is a bar graph comparing the shear adhesion strength of adhesives with different ratios.
[0041] Example 1 Preparation and Application of Adhesive TGO
[0042] Including the synthesis of main agent A lipoic acid derivative sodium salt
[0043] Synthetic route
[0044]
[0045] Synthesis of compound 1
[0046] Add lipoic acid (10.0 g, 48.5 mmol), N,N'-carbonyldiimidazole (8.6 g, 53.3 mmol) and dichloromethane (250 mL) to the reaction vessel, and stir at room temperature for 30 minutes under nitrogen protection. Subsequently, dissolve glycine methyl hydrochloride (6.1 g, 48.5 mmol) and triethylamine (10 mL) in a small amount of dichloromethane (50 mL), add to the above reaction system, and stir at room temperature for 2 hours under nitrogen protection. TLC (thin layer chromatography) tracking monitors the reaction until complete, transfer all solvents to a separatory funnel, extract and wash with 0.5 M citric acid aqueous solution (100 mL), 5 wt% sodium bicarbonate aqueous solution (100 mL×2), saturated brine (100 mL) and deionized water (100 mL), respectively, and dry the organic phase with anhydrous sodium sulfate. The residue was spin-dried and separated by column chromatography (eluent: dichloromethane) to obtain a yellow oily liquid, namely compound 1 (12.8 g, yield 95%). 1 H NMR (600 MHz, DMSO-d 6 ,ppm)δ8.25(t,J=5.9Hz,1H),3.81(d,J=5.9Hz,2H),3.63(s,3H),3.62–3.58(m,1H),3.23–3.09(m,2H),2.42(dq,J=12.5,6.2Hz,1H), 2.14(t,J=7.4Hz,2H),1.88(dq,J=13.5,6.8Hz,1H),1.68(dtd,J=13.5,8.3,5.9Hz,1H),1.59–1.47(m,3H),1.37(p,J=7.1,6.5Hz,2H). 13 CNMR (151MHz, DMSO-d 6 ,ppm)δ173.05,170.97,56.61,52.09,40.96,40.38,38.56,35.25,34.59,28.68,25.39.ESI-MS(m / z):[M+H] + calculated for C 11 H 19 NO 3 S 2 +H:278.0879,found278.0873.
[0047] Synthesis of main agent A
[0048] Compound 1 (12.8 g, 46.0 mmol) and methanol (100 mL) were added to the reaction vessel until completely dissolved, sodium hydroxide (1.8 g, 46.0 mmol) and a small amount of water (10 mL) were added, and heated to reflux at 65°C for 2 hours. After cooling slightly, the mixture was added to the stirring acetone (200 mL) while hot, and a large amount of yellow viscous solid was precipitated. Filtered, washed with dichloromethane, and freeze-dried in a freeze dryer for 5-8 hours to obtain a yellow solid, namely, the main agent A (9.7 g, yield 80%). 1 H NMR (600MHz, D 2 O,ppm)δ3.75(s,2H),3.74–3.69(m,1H),3.28–3.16(m,2H),2.50(dq,J=12.3,6.1Hz,1H),2. 32(t,J=7.5Hz,2H),2.01(dq,J=13.6,6.9Hz,1H),1.82–1.59(m,5H),1.45(p,J=7.7Hz,2H). 13 CNMR(151MHz,D 2 O,ppm)δ176.76,176.63,56.48,43.23,40.24,38.08,35.48,33.75,27.94,24.92.ESI-MS(m / z):[M] - calculated for C 10 H 16 NO 3 S 2 :262.0566,found 262.0580.
[0049] The obtained main agent A is dissolved in water to prepare an aqueous solution with a concentration of 1.0g / 12mL. Doping agent B is not added. Ultrasonic dissolution can be used if necessary to obtain an aqueous solution of TGO adhesive. The obtained yellow aqueous solution of TGO adhesive is directly measured with a pipette to measure 12μL, at which time the solute mass is 1.0mg, and dripped onto a hydrophilic glass sheet (2mm thick), and then covered with another glass sheet, so that the overlapping area is 2.5cm×2.5cm and the aqueous solution is completely wetted, placed in a 60℃ oven and waited for 2 hours, that is, the solute mass ratio of main agent A sodium salt of lipoic acid derivative: doping agent B hexamine is 1.0mg, and the successfully adhered TGO adhesive glass sheet is obtained.
[0050] The obtained TG0 adhered glass sheet was used for load-bearing test. A round hole was made in advance on the glass sheet to facilitate the passing of the rope, and the glass sheet was vertically suspended with an empty bucket hung below. Water or fine sand was added slowly into the bucket until the glass sheet could no longer adhere and broke apart. The total weight of the bucket and the water or fine sand in the bucket was recorded at this time, which was the maximum load-bearing weight when the TG0 adhesive dosage was 1.0 mg and the adhesion area was 2.5 cm×2.5 cm.
[0051] The obtained TGO adhered glass sheet was used for shear adhesion strength test of universal testing machine. The adhered glass sheet was clamped with the fixture of the universal testing machine, and the stretching mode was used with a stretching rate of 1mm / min until the glass sheet could no longer adhere and broke apart. The data was collected and a curve graph of adhesion force and stretching distance was drawn. The shear adhesion strength of the TGO adhesive was calculated based on the maximum adhesion force in the graph divided by the adhesion area.
[0052] Figure 3 This is a TG0 adhesive shear adhesion strength test curve. Figure 3 As shown, the maximum adhesion force is 304.19N, and the shear adhesion strength calculated therefrom is 486.71kPa.
[0053] Example 2 Preparation and Application of Adhesive TG0.5
[0054] The synthesis method of main agent A is the same as that described in Example 1.
[0055] Dissolve the obtained main agent A in water to prepare an aqueous solution with a concentration of 1.0g / 12mL. Ultrasonic dissolution can be used if necessary. After complete dissolution, take out 6mL of the aqueous solution and add 0.25g of dopant B urotropine. After complete dissolution, the aqueous solution of TG0.5 adhesive can be obtained. Take 12μL of the obtained TG0.5 adhesive aqueous solution directly with a pipette. At this time, the solute mass is 1.0mg, and drop it on a hydrophilic glass sheet (2mm thick), and then cover another glass sheet so that the overlapping area is 2.5cm×2.5cm and the aqueous solution is completely wetted. Place it in a 60℃ oven and wait for 2 hours to obtain a successfully adhered TG0.5 adhesive glass sheet.
[0056] The obtained TG0.5 adhered glass sheet was used for load-bearing test. A round hole was made in advance on the glass sheet to facilitate the passing of the rope, and the glass sheet was vertically suspended with an empty bucket hung below. Water or fine sand was added to the bucket slowly and continuously until the glass sheet could no longer adhere and collapsed. The total weight of the bucket and the water or fine sand in the bucket was recorded at this time, which was the maximum load-bearing weight when the amount of TG0.5 adhesive was 1.0 mg and the adhesion area was 2.5 cm×2.5 cm.
[0057] The obtained TG0.5 adhered glass sheet was used for shear adhesion strength test of universal testing machine. The adhered glass sheet was clamped with the fixture of the universal testing machine, and the stretching mode was used with a stretching rate of 1mm / min until the glass sheet could no longer adhere and broke apart. The data was collected and a curve of adhesion force and stretching distance was drawn. The shear adhesion strength of TG0.5 adhesive was calculated based on the maximum adhesion force in the figure divided by the adhesion area.
[0058] Figure 4 This is the shear adhesion strength test curve of TG0.5 adhesive. Figure 4 As shown, the maximum adhesion force is 443.14N, and the shear adhesion strength calculated therefrom is 709.02kPa.
[0059] Example 3
[0060] The synthesis method of main agent A is the same as described in Example 1.
[0061] The obtained main agent A is dissolved in water to prepare an aqueous solution with a concentration of 1.0g / 12mL. Ultrasonic dissolution can be used if necessary. After complete dissolution, 6mL of the aqueous solution is taken out and 0.5g of dopant B hexamethylenetetramine is added. After complete dissolution, the aqueous solution of TG1 adhesive is obtained.
[0062] The use and testing of the adhesive were the same as described in Example 2.
[0063] Figure 5 This is the TG1 adhesive shear adhesion strength test curve. Figure 5 As shown, the maximum adhesion force is 504.56N, and the shear adhesion strength calculated therefrom is 807.30kPa.
[0064] The preparation and application of comparative examples 1-3 correspond to the preparation and application of adhesives TG1.5, TG2 and TG2.5, respectively. The solute mass ratios of TG1.5, TG2 and TG2.5, i.e., main agent A sodium salt of lipoic acid derivative: dopant B hexamine, are 1:1.5, 1:2 and 1:2.5, respectively.
[0065] The synthesis method of main agent A is the same as that described in Example 1.
[0066] The use and testing of the adhesive are the same as described in Example 2.
[0067] Figure 6 This is the TG1.5 adhesive shear adhesion strength test curve. Figure 6 As shown, the maximum adhesion force is 313.05N, and the shear adhesion strength calculated therefrom is 500.88kPa.
[0068] Figure 7 This is the shear adhesion strength test curve of TG2 adhesive. Figure 7As shown, the maximum adhesion force is 243.35N, and the shear adhesion strength calculated therefrom is 389.36kPa.
[0069] Figure 8 This is the TG2.5 adhesive shear adhesion strength test curve. Figure 8 As shown, the maximum adhesion force is 181.82N, and the shear adhesion strength calculated therefrom is 290.91kPa.
[0070] Example 4 Debonding Method of Adhesive TGO
[0071] The TGO adhered glass sheet obtained in Example 1 was placed in water, and the glass sheet separated after a while and lost its stickiness. This meets the requirement of rapid debonding on demand. At the same time, since the amount used is very small and the raw materials are all environmentally friendly raw materials, the impact on the water body after debonding is very small.
[0072] The above examples 1 to 3 illustrate that the hydrophilic adhesive based on sodium salt of lipoic acid derivatives of the present invention has a strong adhesive ability, which exceeds that of many adhesives reported in literature, and is easy to debond, with little residue and little impact on the environment.
[0073] Table 1 summarizes the adhesive properties (1.0 mg dosage, 2.5 cm×2.5 cm adhesion area) for different dopant B contents.
[0074]
[0075]
[0076] As can be seen from Table 1, with the addition of dopant B, the maximum load-bearing capacity, maximum adhesion and shear adhesion strength of the adhesive gradually increase. When the solute mass ratio of the main agent A, sodium salt of lipoic acid derivative: dopant B, hexamethylenetetramine, is 1:1, the performance of the adhesive is the best. However, when the amount of dopant B added is further increased, the performance of the adhesive decreases.
Claims
1. A hydrophilic adhesive based on sodium salt of lipoic acid derivative, characterized in that: The hydrophilic adhesive comprises a main agent A and a dopant B, wherein the mass ratio of the main agent A to the dopant B is 1:(0-1); The main agent A is a monomer in which lipoic acid and glycine are coupled by an amide bond and exist in the form of sodium carboxylate. Its structural formula is shown in Formula A. Dopant B is a commercially available raw material, hexamethylenetetramine, and its structural formula is shown in Formula B.
2. The hydrophilic adhesive according to claim 1, characterized in that The mass ratio of the main agent A to the dopant B in the hydrophilic adhesive is 1:
1.
3. The method for preparing a hydrophilic adhesive according to claim 1, characterized in that: The method comprises the following steps: (1) Preparation of Compound 1: Add lipoic acid, N,N'-carbonyldiimidazole (CDI), and dichloromethane to a reaction flask, wherein the molar ratio of lipoic acid: N,N'-carbonyldiimidazole: dichloromethane is 1:(1.1-1.2):(60-90), and stir at room temperature for 30 minutes. Then, add glycine methyl hydrochloride and triethylamine, wherein the molar ratio of glycine methyl hydrochloride: lipoic acid is 1:1, and the molar ratio of triethylamine: lipoic acid is 1.2:
1. After stirring at room temperature for 2 hours under nitrogen protection, extract and wash, collect and dry the organic layer, remove the organic solvent by rotary evaporation, and purify by column chromatography to obtain a yellow viscous oily liquid to obtain Compound 1; (2) Preparation of main agent A sodium salt of lipoic acid derivative: dissolve the obtained compound 1 in methanol, add a sodium hydroxide aqueous solution with a concentration of 5-10 mol / L, the volume of the sodium hydroxide aqueous solution used should be 1 / 20-1 / 10 of the volume of the methanol used, wherein the molar ratio of the amount of sodium hydroxide solute to compound 1 is (1.1-1.3):1, heat under nitrogen protection and reflux for 2 hours, cool until no longer boiling, add to stirred acetone, and a light yellow to white solid will precipitate, which is collected by filtration, washed and freeze-dried to obtain the target product A; (3) dissolving the obtained main agent A thioctic acid derivative sodium salt in water at a concentration of 1.0 g / 12 mL, and adding the dopant B urotropine, wherein the solute mass ratio of the main agent A thioctic acid derivative sodium salt: the dopant B urotropine is 1:(0-1), to obtain the hydrophilic adhesive based on the thioctic acid derivative sodium salt; The synthetic route of the main agent A lipoic acid derivative sodium salt monomer is as follows:
4. The method for debonding a hydrophilic adhesive as claimed in claim 1, comprising the following steps: (1) Place two adhered glass sheets in water and wait for a while to quickly debond and separate the glass sheets. (2) Rinse the debonded glass with clean water, wipe dry, and then reuse it.